2021
DOI: 10.21203/rs.3.rs-228176/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Auditory Exostosis in Australian Warm Water Surfers: a Cross-sectional Study

Abstract: BackgroundSurfing is a popular sport in Australia, accounting for nearly 10 percent of the population. External auditory exostosis (EAE), also referred to as surfer’s ear, is recognized as a potentially serious complication of surfing. Cold water (water temperature below 19⁰C) is a commonly cited risk factor, with prevalence of EAE in cold water surfers ranging from 61 to 80 percent.However, there is a paucity of studies reporting the prevalence of EAE in surfers exposed to water temperatures above 19⁰C. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In a cross-sectional observational study of 113 Australian surfers, more than half reported seeking medical attention for ear symptoms, including frequent otitis externa, hearing deterioration and water trapping. 16 Exostoses are particularly prevalent among cold water surfers, with the phenomenon demonstrating a doseresponse relationship. 17 Victoria's Surf Coast Shire, seat of what is arguably the spiritual home of surfing in Australia, Bells Beach, is teeming with exostosisafflicted surfers owing to cold water temperatures (with an average of 12.8°C during favourable winter swells), high quality surf spots and an enthusiastic local surfing community.…”
Section: Surfer's Ear In Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional observational study of 113 Australian surfers, more than half reported seeking medical attention for ear symptoms, including frequent otitis externa, hearing deterioration and water trapping. 16 Exostoses are particularly prevalent among cold water surfers, with the phenomenon demonstrating a doseresponse relationship. 17 Victoria's Surf Coast Shire, seat of what is arguably the spiritual home of surfing in Australia, Bells Beach, is teeming with exostosisafflicted surfers owing to cold water temperatures (with an average of 12.8°C during favourable winter swells), high quality surf spots and an enthusiastic local surfing community.…”
Section: Surfer's Ear In Australiamentioning
confidence: 99%
“…Otological sequelae from surfing are common. In a cross‐sectional observational study of 113 Australian surfers, more than half reported seeking medical attention for ear symptoms, including frequent otitis externa, hearing deterioration and water trapping 16 . Exostoses are particularly prevalent among cold water surfers, with the phenomenon demonstrating a dose–response relationship 17 .…”
Section: Surfer’s Ear In Australiamentioning
confidence: 99%